Implementation of restorative justice in the settlement of crimes of persecution by TNI soldiers whose cases have been resolved under customary law - Tiknawan, Rendi Tandang (Goodwood Publishing, 2023)
Purpose: This study aims to analyze the Implementation of Restorative Justice in the Settlement of Criminal Acts of Abuse by TNI Soldiers Whose Cases Have Been Settled According to Customary Law. Research/methodology: In this study, the author uses a qualitative data analysis method, namely data that is described using terms that are separated based on classification to reach a conclusion. To analyze the data, the author uses phenomenology with a descriptive case study design, namely drawing actual events to get a picture of the existing research object, then analyzing it according to the provisions of related laws and regulations, legal theories and opinions of legal experts. Drawing conclusions is done using Deductive Logic. Results: The author concludes that customary law is the basis for the Restorative Justice settlement in criminal acts of abuse committed by TNI soldiers, so the author believes that the Oditur should make and convey a legal opinion to the Case Submitting Officer which can be in the form of a request that the case be resolved according to soldier disciplinary law, or closed for the sake of law, public interest or military interest because the case has been resolved through Restorative Justice by undergoing customary law. Furthermore, after the issuance of Supreme Court Regulation Number 1 of 2024 on the Implementation of Restorative Justice in the settlement of criminal acts of abuse committed by TNI soldiers whose cases have been resolved through customary law or resolved through peace between the defendant and the victim or their heirs before the trial and all agreements have been implemented, the judge can use this as a consideration in the decision and examination process. In the settlement of criminal acts of abuse by TNI soldiers, the victim has been resolved through customary law settlement, this becomes a general requirement by the Judge in imposing a conditional/supervisory criminal sentence.